Evaluation of methods to determine sperm density for the European eel, Anguilla anguilla - Sorensen, S.R.; Gallego, V.; Perez, L.; Butts, I.A.E.; Tomkiewicz, J.; Asturiano, J.F. (Reproduction in Domestic Animals, 2013)
European eel, Anguilla anguilla, is a target species for future captive breeding, yet best methodology to estimate sperm density for application in in vitro fertilization is not established. Thus, our objectives were to evaluate methods to estimate European eel sperm density including spermatocrit, computer assisted sperm analysis (CASA) and flow-cytometry (FCM), using Neubauer Improved hemocytometer as benchmark. Initially, relationships between spermatocrit, hemocytometer counts, and sperm motility were analyzed, as well as the effect of sperm dilution on hemocytometer counts. Furthermore, accuracy and precision of permatocrit, applying a range of G-forces, were tested and the best G-force used in method comparisons. We found no effect of dilution on hemocytometer sperm density estimates, whereas motility associated positively with hemocytometer counts, but not with spermatocrit. Results from all techniques, spermatocrit, CASA and FCM, showed significant positive correlations with hemocytometer counts. The best correlation between spermatocrit and hemocytometer counts was obtained at 6000 × g (r = 0.68). Out of two CASA variants, one or three photographic fields (CASA-1 and CASA-2), CASA-2 showed a very high accuracy to hemocytometer counts (r = 0.93), but low precision (CV: CASA-2 =28.4%). FCM was tested with and without microfluorospheres (FCM-1 and FCM-2,) and relationships to hemocytometer counts were highly accurate (FCM-1: r = 0.94; 45 FCM-2: r = 0.88) and precise (CV: FCM-1 = 2.5; FCM-2 = 2.7%). Overall, CASA-2 46 and FCM-1 feature reliable methods for quantification of European eel sperm, but FCM-1 has a clear advantage featuring highest precision and accuracy. Together, these results provide a useful basis for gamete management in fertilization protocols.